Variability of silver fir (Abies alba Mill.) progeny from the Tisovik Reserve expressed in needle traits and chloroplast microsatellite DNA - Pawlaczyk, Ewa M.; Bobowicz, Maria A. (Biodiversity: Research and Conservation, 2017)
Progeny from nineteen family lines of silver fir (Abies alba Mill.) from the Tisovik Reserve growing in an experimental plot were analyzed based on 4 chloroplast microsatellite DNA loci and 12 morphological and anatomical needle traits. The Tisovik Reserve is located in Białowieża Primeval Forest, 120 km north of the natural range limit of this species, and embraces a small and isolated natural population of silver fir. The aim of this study was to determine genetic variation within and between progeny lines. Analysis of phenotypic variation showed that the traits which differed most among individuals were the needle width and the distance from resin canals to vascular bundle. Those traits, which differed most between the progeny lines, were the number of endodermic cells around the vascular bund and the weight of hypodermic cells. In Tisovik progeny, we detected 107 different haplotypes. In progeny lines, we detected more haplotypes than in maternal trees, and most haplotypes did not exist in maternal trees. This may be the result of pollen influx from other silver fir stands. Progeny from Tisovik showed a higher level of variability in comparison with maternal trees.